G446(P) A systematic review evaluating the methodological quality of infant formula trials. (25th October 2020) - Kunc, M; Dewji, F; Jobson, J; Helfer, B; Boyle, R
Abstract : Background: Infant formula trials are carried out to assess safety and efficacy of infant formula, however an assessment of the risk of bias within these trials is lacking. Furthermore, it is currently unclear whether in these trials breastmilk feeding is appropriately supported. Aims: To assess the risk of bias in infant formula trials and establish whether it varies according to the human development index (HDI). The risk of undermining breastmilk feeding within the trial in relation to the human development index will also be examined. Methods: This systematic review carried out an investigation into controlled trials published from 1/1/16 to 17/2/19, using the Cochrane Risk of Bias 2.0 tool, as well as analysing the risk of undermining breastmilk feeding using signalling questions derived from a previous Delphi consensus. Included trials had a population under 3 years old, where one infant formula was compared against another infant formula with modified ingredients. Results: This study considered 44 main trial publications, where 61% had a high overall risk of bias. In individual domains, highest risk of bias was identified in deviation from intended intervention (36%) and selective outcome reporting (18%). There was no significant association between HDI and risk of bias in any domain (p>0.05). A high risk of undermining lactation tended to be present in lower HDI countries (OR 0.29, 95% CI 0.80 to 1.08, p=0.06). 70% of the trials overall and 63% of those with high risk of undermining lactation were funded by BMS industry. Conclusion: These findings suggest a possible relationship between risk of undermining lactation and HDI, which needs to be explored further. No relationship between risk of bias and HDI was found. Further breastfeeding protection and promotion worldwide is needed.